A blockchain based patient centric electronic health record storage and integrity management for e-Health systems. Issue 4 (December 2021) - CHELLADURAI, Mrs. USHARANI; Pandian, Dr. Seethalakshmi; Ramasamy, Dr. Krishnamoorthy
Highlights of Blockchain based Patient Centric EHR Systems: The proposed system is a Patient Centric secure EHR Management system using Blockchain Technology. The proposed blockchain healthcare system is providing security to health data and privacy to the patient. The proposed system facilitates integration among healthcare providers in order to maintain medical history. The proposed framework allows for a secure health information exchange between the network participants through blockchain technology. The system ensures security, transparency, privacy and interoperability. The proposed system utilizes Modified Merkle Tree for Integrity Management. Abstract: Objectives In the digitization of health records, patients and doctors find difficulty in accessing their health records, especially when the health records are fragmented with different health service providers. In this paper, Patient Centric blockchain smart contracts are designed to provide a regulated solution to the requirements of patients, doctors and health service providers with integrity management. Methods The proposed system launches smart contracts namely i) Registration contract for immutable patient log creation. ii) Health Record Creation Contact to generate digital health records. iii) Health Record Storage Contract for secure storage and rapid access with a new Modified Merkle Tree data structure. iv) Update permission Contract that can provide access at emergency situations. v) Data sharing Permission Contract for exchange of health records between different stakeholders and vi) Viewership Permission Contract for viewing the health information by the patients for home care and future care. Results The work has been carried out on a number of trials to check the effectiveness of the proposed system. The qualitative and quantitative metrics of the proposed system have been measured to evaluate the performance of resources, transactions per second, and the latency of transaction. Conclusion The proposed system provides high security and integrity through cryptographic hash functions. The results are encouraging. The designed system is implemented and found to outperform the existing systems.